Manajemen Baitul Mal Pada Masa Umar Bin Khattab dan Relevansinya terhadap Anggaran Pendapatan dan Pembelanjaan Negara Indonesia - Dania Ivadia Azzahra; Fajar Lazuardy Al-awwabien; Maula Aditya; Anggraeni Olga Umi Nurkhasanah (SIL'AH: Jurnal Ekonomi Syariah, 2026)
The aim of this study is to identify Umar bin Khattab’s policies regarding the sources of income for the Baitul Mal and their relevance to the State Revenue and Expenditure Budget system in Indonesia. This qualitative research, in the form of a literature review, employs a descriptive qualitative approach. Data collection was conducted through documentation. The results indicate that the revenue sources of the Baitul Mal include zakat, kharaj, ushr, khums, jizyah, fai, and ghanimah, which conceptually have a significant correlation with modern state financing instruments. Kharaj can be likened to Land and Building Tax, usyr corresponds to the customs duty system, khums has a functional equivalence to mining tax, and jizyah correlates with the visa mechanism for foreign nationals. This research contributes to the assertion that the fiscal system implemented during the reign of Caliph Umar ibn Khattab can serve as a policy reference for the development of Indonesia’s modern fiscal system.